Arsenophonus, an emerging clade of intracellular symbionts with a broad host distribution - Nováková, Eva (Jihočeská univerzita, 2008)
The thesis brings new phylogenetic data on the rapidly growing bacterial genus Arsenophonus, and summarizes the current evolutionary picture of its symbiotic association with insects and other hosts. The study is prepared in form of a regular publication and will be submitted in microbiological journal.
Arsenophonus, an emerging clade of intracellular symbionts with a broad host distribution
Keywords: symbiotic bacteria; Arsenophonus; phylogeny; symbiotic bacteria; Arsenophonus; phylogeny